2016
DOI: 10.1007/978-3-319-25844-7_15
|View full text |Cite
|
Sign up to set email alerts
|

15 Fruiting Body Formation in Basidiomycetes

Abstract: Growth, Differentiation and Sexuality, 3 rd Edition The Mycota I J. Wendland (Ed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 149 publications
2
18
0
Order By: Relevance
“…How complex multicellularity manifests during fruiting body development has been of interest among mycologists for a long time. Information based on mutant screens and classical genetic techniques (Kues, ; Pöggeler, Nowrousian, & Kück, ; Pelkmans, Lugones, & Wosten, ) is being increasingly complemented by high‐throughput studies based on whole‐genome sequencing and RNA‐sequencing (RNA‐Seq; Nowrousian, ). Studies involving whole‐transcriptome comparisons (Table ) have revealed important principles of fruiting body development in both model and non‐model fungal species.…”
Section: Complex Multicellular Functioning In Fungimentioning
confidence: 99%
“…How complex multicellularity manifests during fruiting body development has been of interest among mycologists for a long time. Information based on mutant screens and classical genetic techniques (Kues, ; Pöggeler, Nowrousian, & Kück, ; Pelkmans, Lugones, & Wosten, ) is being increasingly complemented by high‐throughput studies based on whole‐genome sequencing and RNA‐sequencing (RNA‐Seq; Nowrousian, ). Studies involving whole‐transcriptome comparisons (Table ) have revealed important principles of fruiting body development in both model and non‐model fungal species.…”
Section: Complex Multicellular Functioning In Fungimentioning
confidence: 99%
“…Alongside the model mushrooms Coprinopsis cinerea and Schizophyllum commune , A. aegerita has also been investigated to study the fundamentals of agaricomycete fruit body (mushroom) formation [ 5 , 12 28 ]. Apart from the normal dikaryotic fruit body formation, A. aegerita is also capable of monokaryotic fruiting.…”
Section: Introductionmentioning
confidence: 99%
“…These Principles form the warp and weft of the canvas upon which fungal developmental biology has been built by the cell and molecular biologists of the pre-genomics era. It is now up to the genomic systems analysts to paint the rest of the individual details of the stories on that canvas (Kües & Navarro-González, 2015;Kües et al, 2018;Halbwachs et al, 2016;Pelkmans et al, 2016;Hibbett et al, 2017;Stajich, 2017).…”
Section: Basic Principles Of Fungal Developmental Biologymentioning
confidence: 99%